If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-10=2(x+7)
We move all terms to the left:
5x-10-(2(x+7))=0
We calculate terms in parentheses: -(2(x+7)), so:We get rid of parentheses
2(x+7)
We multiply parentheses
2x+14
Back to the equation:
-(2x+14)
5x-2x-14-10=0
We add all the numbers together, and all the variables
3x-24=0
We move all terms containing x to the left, all other terms to the right
3x=24
x=24/3
x=8
| 11x^2-1020x+11200=0 | | 2m=3.2 | | 2x+x*x*x=30 | | x12=7 | | 72=11x-2 | | 8(y+8)=2y+40 | | 6(3x+2)-5=20x+3 | | 11x^2-1020x-11200=0 | | x+5=-9 | | -77m=7m | | 1/2(10x-6=x-15 | | 1/8n=11n= | | 15g-13g+4g-4g=14 | | a-20=31 | | –7x+15=6 | | 4d=-2 | | 10e-2=29 | | 2(5x-2)-10x=5 | | s/10=7s= | | -2c-12=9c+2 | | u/2=12.8/1 | | 8m=-10m+9m | | -6n+7=31 | | 17w+4w-12w-5w=8 | | -4d=-2 | | 3.6=4tt= | | 2x-3+7x-9=7x+3-2x+9=x= | | 13x-21=10x=51 | | 4r+2r-4r=2 | | 7x+5-2x+8=2x | | 2.5=10m= | | 5r+4r-2r-7r+4r=16 |